2007
DOI: 10.1007/s00467-006-0329-6
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-Mg2+-dependent ATP-ase activity and calcium homeostasis in children with chronic kidney disease

Abstract: Extracellular calcium concentrations in humans are thousands times higher than within cells. Maintenance of such gradient requires specific regulation including intracellular stores, Ca binding proteins and transmembrane protein systems. The aim of the study was to estimate PMCA (plasma membrane Ca-transporting adenosine triphosphatase; ATPase 3.6.1.38) activity and calcium homeostasis in erythrocytes of children with chronic kidney disease (CKD). Twenty-one children wth CKD stages 1-3 (group I) and 18 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…All children in our study had features of hyperparathyroidism, which might have been one of the reasons for increased calcium influx into erythrocytes. Increased Ca i 2+ level in erythrocytes may also result from reduced PMCA activity, which was documented for both children and adults with CKD treated conservatively, as well as in adults on renal replacement therapy [5, 6, 10]. Results of the present study are compatible with the above observations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…All children in our study had features of hyperparathyroidism, which might have been one of the reasons for increased calcium influx into erythrocytes. Increased Ca i 2+ level in erythrocytes may also result from reduced PMCA activity, which was documented for both children and adults with CKD treated conservatively, as well as in adults on renal replacement therapy [5, 6, 10]. Results of the present study are compatible with the above observations.…”
Section: Discussionsupporting
confidence: 91%
“…Our earlier studies have revealed that children and adolescents with CKD stages 2–4 are characterized by a reduced PMCA activity in erythrocytes accompanied by a CALM deficit and disturbances in the CANP-CAST system [5, 6]. The changes result in a high intracellular calcium level.…”
Section: Introductionmentioning
confidence: 99%
“…[25,26] , by the enhanced calcium influx [9] and the increase in intracellular calcium reserves [10] . The main mechanism of the lymphocyte [Ca 2+ ] i increase involves CRAC channels.…”
Section: Discussionmentioning
confidence: 99%
“…Massry et al have previously demonstrated that basal levels of [Ca 2þ ] i are greater in several other CKD cell types, including cardiomyocytes [24,25], brain synaptosomes [26], pancreatic islets [27], polymorphonuclear leukocytes [28][29][30], T-cells [31], and platelets [32], and suggested elevated parathyroid hormone (PTH) as a causative factor. Polak-Jonkisz et al [33] identified increased [Ca 2þ ] i in erythrocytes of children with CKD. Lajdova et al [34] isolated human peripheral blood mononuclear cells from 44 adult CKD patients with CKD stage 2-3 and found increased [Ca 2þ ] i in CKD cells compared with normal cells.…”
Section: Introductionmentioning
confidence: 99%